DATUK SUDIRMAN AGUS SENIMAN DAN BUDAYAWAN DI KABUPATEN KAMPAR (1987-2019) - Amalia Wirda; Isjoni Isjoni; Ahmal Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Datuk Sudirman Agus is one of the leading artists and cultural observers who have preserved Malaysian culture in Kampar Regency. Datuk Sudirman Agus is the first of 9 children. His father was called Said Agustami and his mother was called Raja Hj. Daramah RHK. Datuk Sudirman Agus was born in Jerambang Village, Gaung Anak Serka Subdistrict, Inderagiri Hilir Regency on September 9, 1949. Datuk The objectives of this study are: (1) To determine the background of Datuk Sudirman Agus's life as an artist and cultural figure in Kampar Regency, (2) To discover the role of Datuk Sudirman Agus as an artist and cultural figure in the preservation of Malaysian culture in Kampar Regency, (3) This is to establish the award that Datuk Sudirman Agus received. The result of this research is the role of Datuk Sudirman Agus in the preservation of Malaysian culture in Kampar district, developing and preserving Malaysian culture in Kampar in the form of his works, preserving the existing Malay culture in Kampar district Kampar by creating art performances with nuances of Kampar Malaysian culture, making books on Kampar history and culture, there are Kampar customs, writing books on Kampar local content, researching the values living in the Kampar community. He fights for intellectual works of art as cultural heritage of Kampar and he preserves the Malaysian culture of Kampar at the national and international level. So he received an award as an ambassador of Malaysian Riau culture from Kampar Regency and received the intellectual remembrance of Riau Malay Traditional Institute for his work and dedication to Riau Malay culture.Key Words: Datuk Sudirman Agus, Role, Artist and Humanist